Filsafat Manajemen - Abdul wahid mahsuni; Novia putri oktaviani; Arif akbarrurrijal; Shabrina ayu hananta (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Management philosophy is a collection of knowledge and beliefs that provide a broad basis or basis for determining problem solving. The method in this article uses the literature method, is a study that studies various reference books and similar previous research results to obtain a theoretical basis for the problem to be studied. The data collection uses how to find sources and construct from various sources such as books, journals and research that has been done. Four perspectives from the formation of epistemology and ontology provide a framework for management to know how they act as managers of an organization. This perspective as a basic form of manager's reasoning in action and how to assess individual behavior in the organization